A Nitrogen‐Rich 2D sp2‐Carbon‐Linked Conjugated Polymer Framework as a High‐Performance Cathode for Lithium‐Ion Batteries. (11th December 2018) - Xu, Shunqi; Wang, Gang; Biswal, Bishnu P.; Addicoat, Matthew; Paasch, Silvia; Sheng, Wenbo; Zhuang, Xiaodong; Brunner, Eike; Heine, Thomas; Berger, Reinhard; Feng, Xinliang
Abstract: A two‐dimensional (2D) sp 2 ‐carbon‐linked conjugated polymer framework (2D CCP‐HATN) has a nitrogen‐doped skeleton, a periodical dual‐pore structure and high chemical stability. The polymer backbone consists of hexaazatrinaphthalene (HATN) and cyanovinylene units linked entirely by carbon–carbon double bonds. Profiting from the shape‐persistent framework of 2D CCP‐HATN integrated with the electrochemical redox‐active HATN and the robust sp 2 carbon‐carbon linkage, 2D CCP‐HATN hybridized with carbon nanotubes shows a high capacity of 116 mA h g −1, with high utilization of its redox‐active sites and superb cycling stability (91 % after 1000 cycles) and rate capability (82 %, 1.0 A g −1 vs. 0.1 A g −1 ) as an organic cathode material for lithium‐ion batteries.